Defining the Value of a School Subject - Hardy, Alison (PRISM: Casting New Light on Learning, Theory and Practice, 2018)
One consequence of school performance measures is the prioritisation of some school subjects above others. The English Baccalaureate (EBacc), introduced in England in 2011, measures pupils’ progress in five subjects only (English, mathematics, science, a humanities subject and a language), and excludes creative subjects such as design and technology (D&T). This suggests that some subjects have greater value than others but the justification for some subjects' inclusion and others’ exclusion has been based on a perspective that draws on ideas from Hirsch (2006) and Young (2008). Counter arguments to this perspective have tended to focus on the economic and intrinsic value of the excluded subjects. This suggests that school subjects do have multiple values. The aim of this research is to establish a framework that could be used to explore and define the value of a school subject.Once the subject-value framework was established it was tested using data gathered from interviews with people who had an interest in education and specifically, D&T. The values they attributed to D&T, such as how it might benefit pupils whilst at school and in later life, were explored and analysed using the framework. The results suggest that the constructed subject-value framework can be used to analyse the values individuals attribute to a school subject. A range of goals and benefits related to the subject can be determined, although distinguishing between the different types of goals needs further research.Most values identified focused on how D&T helped individuals prepare for life beyond school. Additionally, the values reflected the economic justification for education, inasmuch that pupils learn skills in D&T they can use in future careers.This constructed subject-value framework could be used as a means of analysing curriculum policy as it influences the values different people attribute to a subject. Further work could assess if this paper’s findings are replicable or similar by testing the framework against other non-Ebacc subjects.